Contact with Nature as Essential to the Human Experience: Reflections on Pandemic Confinement. Issue 2 (1st June 2021) - Kazdin, Alan E.; Vidal-González, Pablo
Abstract: Human contact with nature is more important than ever before considering the global confinement brought about by the COVID-19 pandemic, the increased urbanization of society, and increased rates of mental disorders and threats to human well-being. This article conveys the importance of contact with nature from three perspectives: historical, sociocultural, and scientific. These perspectives convey the many ways in which contact with nature is essential to human life, the multiple ways in which this is expressed, and the broad range of benefits this has. The case for preserving the natural environment continues to be made in light of the dangers of climate change, the deleterious effects of pollution, and the importance of habitats. We add to the case by underscoring how human well-being has depended on contact with natural environments and how the need for this contact is more salient now than ever before.